Hierarchical nickel/phosphorus/nitrogen/carbon composites templated by one metal–organic framework as highly efficient supercapacitor electrode materials. Issue 6 (24th January 2019) - Yu, Fan; Xiong, Xin; Zhou, Liu-Yin; Li, Jia-Luo; Liang, Ji-Yuan; Hu, Si-QIan; Lu, Wang-Ting; Li, Bao; Zhou, Hong-Cai
Abstract : Novel carbon materials containing Ni, P, N and O were fabricated from the sacrificial MOF template, which exhibits high performance in electrochemical energy storage. Abstract : Utilization of a proper metal–organic framework (MOF) template has recently attracted significant attention for the fabrication of high-performance supercapacitor electrodes; however, limited attention has been paid to the process of preparation of an excellent MOF template used to derive the anticipated electrode materials. Herein, a two-fold interpenetrating MOF with a microporous structure and multi-components, such as nickel, phosphorus, nitrogen, oxygen, and carbon, in the final framework was successfully constructed. The pristine sample could be directly utilized as a supercapacitor electrode material, which exhibited the moderate electrochemical capacitance of 979.8 F g −1 at the current density of 1 A g −1 . Using the simple treatment of one-step pyrolysis under a nitrogen atmosphere at different annealing temperatures (500 °C, 600 °C, 700 °C, and 800 °C), rare hierarchical Ni/P/N/C composites, denoted as Ni/P/N/C-500, Ni/P/N/C-600, Ni/P/N/C-700, and Ni/P/N/C-800, were derived from the parent MOF. The anticipated multi-components Ni, P, N, and O were uniformly incorporated into the carbon materials, which resulted in an excellent synergistic effect to improve the electrochemical energy storage performance. The morphologies and components of these derivatives were characterized via SEM, XPS, and XRD, indicating the uniform distribution of different components in the hybrid structures. The maximum specific capacitance for the Ni/P/N/C-500 electrode reached 2887.87 F g −1 at the current density of 1 A g −1, which was superior to that of other hierarchical composites and established a new benchmark in the related field. The combination of several advantages, such as high surface area, even distribution, and ultra-high content of Ni/P/N/C components, in these derivatives ensured their high-performance in energy storage. The presented results fully demonstrate the unique advantage of utilizing the pre-designed MOFs as a template to prepare hybrid materials used as potential electrode-active materials in supercapacitors and provide an efficient route to fabricate superior-performance energy-storage devices.